Using performative knowledge production to explore marketplace exclusion. Issue 4 (11th September 2017) - Burgess, Gemma; Kelemen, Mihaela; Moffat, Sue; Parsons, Elizabeth
Abstract : Purpose: This paper aims to contribute to understandings of the dynamics of marketplace exclusion and explore the benefits of a performative approach to knowledge production. Design/methodology/approach: Interactive documentary theatre is used to explore the pressing issue of marketplace exclusion in a deprived UK city. The authors present a series of three vignettes taken from the performance to explore the embodied and dialogical nature of performative knowledge production. Findings: The performative mode of knowledge production has a series of advantages over the more traditional research approaches used in marketing. It is arguably more authentic, embodied and collaborative. However, this mode of research also has its challenges particularly in the interpretation and presentation of the data. Research limitations/implications: The paper highlights the implications of performative knowledge production for critical consumer learning. It also explores how the hitherto neglected concept of marketplace exclusion might bring together insights into the mechanics and outcomes of exclusion. Originality/value: While theatrical and performative metaphors have been widely used to theorise interactions in the marketplace, as yet the possibility of using theatre as a form of inquiry within marketing has been largely neglected. Documentary theatre is revealing of the ways in which marketplace cultures can perpetuate social inequality. Involving local communities in the co-production of knowledge in this way gives them a voice in the policy arena not hitherto fully addressed in the marketing field. Similarly, marketplace exclusion as a concept has been sidelined in favour of marketplace discrimination and consumer vulnerability – the authors think it has the potential to bring these fields together in exploring the range of dynamics involved.